Success status of Barangay Micro Business Enterprise (BMBE) in relation to proprietors' understanding and capacity in business operations: gateway to orientation program - Enderina, Randy D. (Parañaque City: Olivarez College, 2019)
RA 9178 modified RA 6977, called the Barangay Micro Business Enterprises Act. Proprietor's awareness and competence in business operations within the Barangay Micro Business Enterprise's (BMBE) context is a poor representation of these concerns. This article intends to investigate the capacities and levels of understanding of BMBE owners, focusing on topics in Imus, Cavite. This is followed by the examination of BMBE owners' capabilities while conducting a firm along with their capabilities. The conclusions will be formed regarding the probable consequences for an orientation program that is believed to be an intervention to aid improved business operations of BMBES. The orientation training may be the best approach of training BMBE owners on the BMBE law, basic company operations ideas, business decision making and leadership. Additionally, the researcher pursued the study to find out if business owners lacked a grasp of their profitability, entrepreneurial knowledge, and capability to function. In more recent years, nevertheless, there has been a movement towards a more comprehensive model of knowledge and the ability to run a firm. For the most part, this position had the business and its owners (who were ready) in the center. The Act, therefore, strives to incorporate micro-enterprises in the informal sector into the mainstream economy. In Small business interest in the Philippines rose due to individualistic perceptions of entrepreneurship. Seedbeds of Filipino entrepreneurial potential are vital for the country's economic progress.
Master Thesis
Keywords: Barangay Micro Business Enterprise; Orientation program; Business operation